Minimally invasive parathyroid carcinoma—A missing entity between parathyroid adenoma and carcinoma: Scintigraphic and histological features. (3rd October 2019) - Singh, Priyanka; Vadi, Shelvin Kumar; Saikia, Uma Nahar; Sood, Ashwani; Dahiya, Divya; Arya, Ashutosh Kumar; Behera, Arunanshu; Mukherjee, Soham; Arvindkumar, Sapara Mohin; Bhadada, Sanjay Kumar
Abstract: Purpose: Minimally invasive parathyroid carcinoma (MIPC) is clinically and biochemically comparable with parathyroid adenoma (PA) though histopathologically differ from PA. MIPC is an intermediate of PA and parathyroid carcinoma (PC). In literature, there is no definite criterion to diagnose MIPC. Our aim was to evaluate and characterize the imaging and biochemical parameters with histological characteristics of MIPC. Methodology: Ten patients with MIPC were recruited from (single centre) Indian PHPT registry (www.indianphptregistry.com ) from January 2014 to July 2018. Clinical, biochemical, imaging and histological features of MIPC patients were reviewed. Results: The mean age of MIPC patients (n = 10; 3 males) was 39.9 ± 11.3 years (range: 17‐50). All patients had an elevated preoperative parathyroid hormone (iPTH) level ranging from 427 to 2138 pg/mL (median: 1328). MIBI scan showed intensely avid and enlarged parathyroid tumours in all patients; LIPT in 6, RIPT in 3 and ectopic mediastinal in 1 with mean size of the tumours was 2.8 ± 1.1 cm. The mean of maximum standardized uptake value (SUVmax) of MIPC in F‐18 fluorocholine PET/CT was 6.7 ± 1.1 (range 6.0‐8.3). The mean tumour weight was 12 ± 9.5 g (range: 1.09‐28). All MIPC patients had identified capsular invasion in 80% and vascular invasion in 50% only but there was no local invasion, lymph nodal or distant metastasis. The mean Ki‐67 labelling index was 3.2 ± 2.7 (range 1.1‐10). Conclusion: The study concluded that MIPC patients are less aggressive (on the basis of imaging and histopathological findings) and should be differentiated from parathyroid adenoma and carcinoma.